2018
DOI: 10.1016/j.jegh.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, Socio-economic and Lifestyle Determinants of Under- and Over-nutrition among Bangladeshi Adult Population: Results from a Large Cross-Sectional Study

Abstract: Bangladesh is currently going through a nutritional transition with rapid increase in overnutrition while undernutrition is still remaining prevalent. Nevertheless, population-based data on demographic, socioeconomic and lifestyle factors associated with underweight and overweight among adult population is scarce. Employing a nationwide cross-sectional survey, we collected anthropometric, demographic, socioeconomic , lifestyle and dietary information from 12,180 adults aged ≥35 years. Body Mass Index (BMI) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A recent meta-analysis has shown that overall prevalence for metabolic syndrome (a cluster of health problems including high blood pressure, abdominal fat, high triglycerides, high blood sugar, and low HDL cholesterol) is higher in Bangladesh compared to the estimated world prevalence (30% versus 20-25%) (3). Besides, approximately 34% of adults are overweight and NCDs account for 67% of deaths in Bangladesh (4,5).…”
mentioning
confidence: 99%
“…A recent meta-analysis has shown that overall prevalence for metabolic syndrome (a cluster of health problems including high blood pressure, abdominal fat, high triglycerides, high blood sugar, and low HDL cholesterol) is higher in Bangladesh compared to the estimated world prevalence (30% versus 20-25%) (3). Besides, approximately 34% of adults are overweight and NCDs account for 67% of deaths in Bangladesh (4,5).…”
mentioning
confidence: 99%